2005
DOI: 10.1007/s10802-005-7650-6
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Family-Centered Interventions Within the Public Middle School: Linking Service Delivery to Change in Student Problem Behavior

Abstract: The Adolescent Transitions Program is a family-centered intervention strategy designed to reduce problem behavior and prevent drug use within a public school environment. A parent consultant within a Family Resource Center (FRC) provided universal, selected, and indicated interventions that enhanced and supported positive parenting practices known to serve as protective factors. Implementation of the 3-year FRC model involved 584 students and their families in 4 middle schools. Analyses focused on the dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 135 publications
(99 citation statements)
references
References 60 publications
3
91
1
4
Order By: Relevance
“…The final recruitment rate by wave and school varied from 58 to 81 percent, with an unweighted mean of 70 percent. Further procedural details are available elsewhere (Stormshak, Dishion, Light, & Yasui, 2005).…”
Section: Siena Models Of Social Ecologiesmentioning
confidence: 99%
“…The final recruitment rate by wave and school varied from 58 to 81 percent, with an unweighted mean of 70 percent. Further procedural details are available elsewhere (Stormshak, Dishion, Light, & Yasui, 2005).…”
Section: Siena Models Of Social Ecologiesmentioning
confidence: 99%
“…In one middle school, the parent consultant established a coffee cart for parents and would meet them as they dropped off their middle school child and picked up coffee. In this study, we found that the number of parent contacts in Grades 6, 7, and 8 was associated with reductions in growth in teacher ratings of risk (Stormshak et al, 2005).…”
Section: Engagementmentioning
confidence: 54%
“…Family-centered interventions have undergone a critical shift in the past 20 or so years, having moved from a treatment model that is delivered to clients in clinic settings to an intervention model involving proactive recruitment of parents to engage in interventions in community settings such as schools (Stormshak, Dishion, Light, & Yasui, 2005). The approach described in this volume is potentially applicable to implementation in several service settings, including preschools and welfare programs' family services (Shaw, Dishion, Supplee, Gardner, & Arnds, 2006), and is especially designed for public school settings .…”
mentioning
confidence: 99%
“…This 44-item measure, based on Soberman (1995) and modified by Stormshak, Dishion, Light, and Yasui (2005), includes items on a variety of risk and positive behaviors that teachers suspect or know youth may be engaged in, including subscales used in this study related to three areas: Attention Problems (10 items with an internal consistency α = 0.95), Sadness, Aloneness, or Depression (7 items, α = 0.90), and Suspicion of Drug/Alcohol Use (2 items, α = 0.89). Each of the items was rated on a 10-point Likert-type scale ranging from 1 (no problem at all) to 10 (clear and frequent signs).…”
Section: Teacher Questionnaire Teachers Completed the Teacher Measurmentioning
confidence: 99%